2022
DOI: 10.3389/fpls.2022.866211
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Locus RsCr6 Related to Clubroot Resistance in Radish (Raphanus sativus L.)

Abstract: Clubroot is a devastating disease that causes substantial yield loss worldwide. However, the inheritance and molecular mechanisms of clubroot resistance during pathogen infection in radish remain largely unclear. In this study, we investigated the inheritance of clubroot resistance in the F2 population derived from crossing clubroot-resistant (CR) and clubroot-susceptible inbred lines “GLX” and “XNQ,” respectively. Genetic analysis revealed that a single dominant gene controlled the clubroot resistance of “GLX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Gan et al identified five QTL loci, RsCr1, RsCr2, RsCr3, RsCr4, and RsCr5, associated with clubroot disease resistance, with RsCr1 being homologous to the well-defined locus Crr1 [107]. Recently, Gan et al identified a new locus RsCr6 on chromosome 8 and screened for possible resistance candidate genes R120263140 and R120263070 [108].…”
Section: Clubroot Resistance (Cr) Genes and Resistance Breeding In Br...mentioning
confidence: 99%
“…Gan et al identified five QTL loci, RsCr1, RsCr2, RsCr3, RsCr4, and RsCr5, associated with clubroot disease resistance, with RsCr1 being homologous to the well-defined locus Crr1 [107]. Recently, Gan et al identified a new locus RsCr6 on chromosome 8 and screened for possible resistance candidate genes R120263140 and R120263070 [108].…”
Section: Clubroot Resistance (Cr) Genes and Resistance Breeding In Br...mentioning
confidence: 99%
“…Soilborne plant pathogens can be highly devastating in terms of crop health, yield, and economic sustainability, and the chemical strategies currently deployed to combat these pathogens have often proven inadequate (Delgado-Baquerizo et al, 2020). Clubroot, for example, is one of the most destructive soilborne diseases of plants in the Brassicaceae family, which provides the second-largest source of vegetable oil and third largest source of vegetables, including rapeseed, mustard, radish, cabbage, kohlrabi, cauliflower, and broccoli (Gan et al, 2022; Hasan et al, 2021; FAO 2020). This disease is caused by an obligate biotrophic protist, Plasmodiophora brassicae , which can survive in the soil as long-lived resting spores.…”
Section: Introductionmentioning
confidence: 99%
“…Clubroot disease is a rapidly increasing and serious destructive factor affecting the yield and quality of radishes. In China, radish Agronomy 2024, 14, 157 2 of 12 clubroot disease occurs in provinces including Yunnan, Sichuan, Hubei, Henan, etc., to varying degrees annually, causing serious economic losses [10,11].…”
Section: Introductionmentioning
confidence: 99%